ANALISIS PENGARUH PROFITABILITAS KEPUTUSAN INVESTASI KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan yang Terdaftar di Jakarta Islamic Index Tahun 2011-2015) - Kurniawan, Noval; Mawardi, Wisnu (Diponegoro Journal of Management, 2017)
The main goal of the company is to maximize shareholder wealth, and it can be achieved by maximizing the value of company. This study is aim to examine the effect of profitability, investment decision, financing decision, dividend policy to the firm value. Return On Asset (ROA) was used as a proxy of profitability, Total Asset Growth (TAG) was used as a proxy of investment decision, Debt to Equity Ratio (DER) was used as a proxy of financing decision, Dividen Payout Ratio (DPR) was used as a proxy of dividend policy and Price Book Value (PBV) was used as a proxy value of the firm. This results partially on profitability (ROA) and invesment decision (TAG) have the positive and significant effect to the firm value (PBV). In contrast, financing decision (DER) and dividend policy (DPR) has the positive and unsignificant effect to the firm value (PBV). Simultaneously, the four independent variables that affect the company's variable value (PBV), but the value of the company is not only influenced by internal factors, the company's value is also influenced by external factors such as interest rates, inflation rates, exchange rates and social and political situation.